UPAYA PENCEGAHAN PENYEBARAN PENYAKIT DEMAM BERDARAH DENGUE DENGAN MELAKUKAN SURVEILANS LARVA NYAMUK Aedes spp. - Tasya Febrial (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Dengue Hemorrhagic Fever (DHF) is one of the public health important viral disease because. The location of the village is close to the Mount Halimun Salak National Park, the plants vegetation is relatively dense and high rainfall each year. High rainfall in the village can cause containers outside the house to fill with rainwater, this will provide a breeding ground for mosquito growth. The environment around the house where there is still plant vegetation that can function as a habitat and resting place for mosquitoes, especially mosquitoes of the genus Aedes. This community service aims to increase community knowledge about dengue disease in order to prevent the spread of dengue disease. The method used is counseling and larval surveis directly to residents' homes. The results of community service showed that Aedes aegypti mosquito larvae were found in 8 residents' houses. The mosquito larvae of Ae. aegypti which is a vector of dengue disease indicates that it is still possible for the spread of dengue disease. For this reason, a regular and continuous mosquito larvae inspection program is needed.